Trabalho Colaborativo Entre Professoras da Sala de Recursos Multifuncional: proposições didático pedagógicas para alunos com deficiência intelectual dos anos finais do ensino fundamental - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
This research aimed to know the work developed by eight teachers in the Multifunctional Resource Room (SRM) of the state education network in the municipality of Ponta Grossa - PR. We held meetings via Google Meet to discuss the teaching work at SRM and learn about the pedagogical didactic resources used by the research participants. We work with a collaborative research approach, of an applied nature, adopting participatory research procedures, based on a bibliographic survey that supported our actions. The focus of the study is aligned with the contents of Portuguese and Mathematics from 6th to 9th grade. We held discussions to identify the work methodologies used by the teachers at SRM and reformulated the didactic proposals exposed by them so that they could be developed with their SRM students. Once this process is over, we highlight the results of the students in carrying out the activities and together we arrive at some didactic-pedagogical proposals that may subsidize the work of other teachers at SRM who work with students in the final years of elementary school. Through our study, it was possible to perceive that collaborative work contributed to the professional enrichment of all research participants who had the opportunity to present their didactic productions to the group and at the same time get to know the productions of their colleagues. We realize the importance of didactic structuring in a collaborative way aimed at curricular adaptations, thus benefiting students with more attractive and age-appropriate materials. We saw that collaborative work gives teachers the opportunity to share ideas and activities, optimizing the didactic organization in the daily life of schools.
Keywords: Educação Inclusiva; Trabalho Colaborativo; Deficiência Intelectual; Anos Finais do Ensino Fundamental; Sala de Recursos Multifuncional; inclusive education; collaborative work; intellectual disability; final years of elementary school; multifunctional resource room; CNPQ::CIENCIAS HUMANAS::EDUCACAO